Customer Relationship Management with Reference to Products of High Customer Involvement - Chopra, P. K.; Mishra, P. K. (Indian Journal of Marketing, 2010)
This study aims to develop a model of Dynamic Communication (information seeking) instrument (DCI) which can prove useful to all customer relationship executives for various types of customers (e.g. vocal, non vocal, and quasi vocal) of products which require their high involvement. The six dimensions of inter personal skills were conceived after a pilot study. These dimensions are mentioned below: 1. Appearance - Customer relationship executive’s visual appeal and regular visits. 2. Approach - to seek permission and state the purpose. 3. Conversationalisation - to exchange useful information with customer. 4. Convincing - elicit trust and confidence for approval and agreement. 5. Handling objections - ability to provide solutions. 6. Achieving objectives - Getting the desired goals.